2019
DOI: 10.1080/19420862.2019.1668226
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of light and heavy antibody chains using ion mobility and middle-down mass spectrometry

Abstract: The analysis of monoclonal antibodies (mAbs) by a middle-down mass spectrometry (MS) approach is a growing field that attracts the attention of many researchers and biopharmaceutical companies. Usually, liquid fractionation techniques are used to separate mAbs polypeptides chains before MS analysis. Gas-phase fractionation techniques such as high-field asymmetric waveform ion mobility spectrometry (FAIMS) can replace liquid-based separations and reduce both analysis time and cost. Here, we present a rapid FAIM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 44 publications
4
36
0
Order By: Relevance
“…Analysis of TDS with FAIMS and employing a CV of -30V resulted in a waveform that favored the stable trajectory of only ubiquitin as shown on the second panel of Figure 1. As the CV was increased by 10V in subsequent LC injections, the remaining protein standards were observed with larger protein species generally preferring more positive CVs, consistent with previous observations 21 (Figure 1). The exception among the standards was trypsinogen, which contains disulfide bonds.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Analysis of TDS with FAIMS and employing a CV of -30V resulted in a waveform that favored the stable trajectory of only ubiquitin as shown on the second panel of Figure 1. As the CV was increased by 10V in subsequent LC injections, the remaining protein standards were observed with larger protein species generally preferring more positive CVs, consistent with previous observations 21 (Figure 1). The exception among the standards was trypsinogen, which contains disulfide bonds.…”
Section: Resultssupporting
confidence: 90%
“…Its use in TDP analysis has been limited, with most investigators studying intact protein standards. Investigators employing ion-mobility-time-offlight mass spectrometry systems have shown that IMS influences the arrival time distribution of different peptides, denatured protein charge states and multimeric native protein structures [17][18][19][20] Our previous study employed static electrospray ionization (ESI) coupled with a commercial implementation of FAIMS to separate and analyze a simple mixture of heavy and light chains from a monoclonal antibody 21 . Without gas-phase fractionation, the light chain dominates the precursor ion signal in MS experiments, resulting in low signal-to-noise and poor detection of the heavy chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Localization of PTMs to an individual subunit is also beneficial for the assessment of critical quality attributes. [8][9][10] Subunit production is often carried out by non-biological chemical reaction and/or enzyme digestion. 10,11 Consistent subunit production is essential in middle-up and middledown mass spectrometry workflows requiring effective reduction steps.…”
Section: Introductionmentioning
confidence: 99%
“…34 To prevent collision of the ions with the electrode, a deviation in the ion's path is introduced through the application of a DC compensation voltage (CV), 35 allowing selective transmission of that ion. 34 The application of FAIMS to intact protein analysis has largely been restricted to the separation of conformers of individual proteins or small combinations of proteins, [36][37][38][39][40][41] however, FAIMS has recently been applied to intact and native protein analyses using liquid extraction surface analysis (LESA). [42][43][44][45][46] Here we apply FAIMS-TDP analysis to a whole-tissue sample from the medial frontal cortex (MFC) of an Alzheimer's patient.…”
Section: Introductionmentioning
confidence: 99%